ANALISIS YURIDIS PENERAPAN UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERKAIT DENGAN PENYEBARAN UJARAN KEBENCIAN MELALUI MEDIA SOSIAL - Pane, Relly Rakhmani; Purba, Nelvitia; Mustamam, Mustamam (Jurnal Ilmiah METADATA, 2021)
The dissemination of information containing hate speech content has been formulated as a criminal offense or prohibited act as formulated in Article 27 paragraph (3) in conjunction with Article 28 Paragraph (2). Violation of this article is punishable by criminal sanctions as stipulated in Article 45, namely a maximum penalty of 6 years in prison and a maximum fine of Rp. 1,000,000,000., (One billion rupiah). Law enforcement with the application of the ITE Law on the freedom of expression of citizens, currently has an impact on freedom of expression and opinion, especially in relation to the freedom conveyed by a person or group of people in criticizing government policies. Protection of the freedom of expression of citizens in relation to the application of the ITE Law. Until now, there is no policy direction in the ITE Law that describes the protection of freedom of expression and opinion for every citizen. The revision of the ITE Law, has not shown any substantive changes that provide freedom for citizens to express their opinions.